Alterações ultrassonógráficas de 2° e 3° trimestres observadas em 143 fetos submetidos ao estudo cromossômico e acompanhados no Centro de Medicina Fetal / UFMG - Renato Janone Domont (2003)
Purpose: To describe the ultrasonographic findings observed in 143 fetuses, associating them with the main chromosomal anomalies and verifying if there is a typical ultrasonographic alteration that could be related to a particular chromosomopathy. Method: A retrospective and descriptive study was carried out including 143 fetuses with ultrasonographic abnormalities followed up from January 1997 to June 2003. Charyotyping was made in all cases. The material used was obtained by invasive techniques. Results: The cordocentesis was the most common invasive technique performed with 103 punctures. Of the followed 143 fetuses, 66 (46,1%) had chromosomal disease. Themost common chromosomal anomaly in our experience was trisomy 18, with 22 cases (33,3%) followed by trisomy 21, with 15 cases (22,7%). 45% of the fetuses with two or more ultrasonographic abnormalities had a chromosomal anomaly. 78% had cromosomopaties when seven or more structural defects were observed by ultrasound. The cardiac anomalies (especially ventricular septal defects) were the most frequentfinding in fetuses with trisomy 21 (46,7%). At the trisomy 18 the polyhydramnios (72,7%) and intrauterine growth restriction (63,3%) were the most frequent ultrasonographic finding. The cleft lip (88,9%) and the intrauterine growth restriction (55%) were more frequent in fetuses with trisomy 13. Conclusions: The risk of chromosomal diseases increases according to the growth in the number of abnormalities seen by ultrasound examinations.